Safety management in construction: 20 years of risk modeling. (September 2020) - Alkaissy, Maryam; Arashpour, Mehrdad; Ashuri, Baabak; Bai, Yu; Hosseini, Reza
Highlights: Safety is correlated with project performance metrices such as quality, cost and productivity. Integrated risk modeling approaches are better suited for construction safety management. Contemporary literature of the safety risk modeling has been reviewed. Abstract: Construction industry has one of the highest rates of fatalities and injuries compared to other industries, despite technological advancements and implementations of occupational health and safety initiatives. In this paper, a systematic review has been conducted on the contemporary literature of safety risk management. The interface with system modeling has been investigated to identify correlations between the two, and opportunities for improving project performance metrics such as quality, productivity, and cost. Findings show that simulation and optimization technics have advanced in the past 20 years but there is room for improvement when it comes to modeling safety related risks. This review paper contributes to the literature of safety management by providing insight into dynamics of different simulation and optimization modeling techniques. Future research opportunities have been identified including the need for construction safety research on integrating multi-method modeling approaches.